2001
DOI: 10.1007/bf03162316
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of electron spin relaxation for threeS = 1/2 species doped into diamagnetic solid hosts

Abstract: Electron spin lattice relaxation rates (1/T1 ) were measured as a function of temperature at two or three microwave frequencies for three S = 1/2 species in temperature ranges with different dominant relaxation processes. Between 10 and 50 K the contribution from the direct process to the relaxation rate was substantially greater at 94 than at 9.5 GHz for a vanadyl porphyrin doped into zinc tetratolylporphyrin. For bis(diethyldithiocarbamato)copper(TI) doped into the diamagnetic Ni(II) analog the relaxation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 21 publications
4
50
1
Order By: Relevance
“…Based only on the temperature dependence of 1/T 1 over a limited temperature interval at a single microwave frequency it is not possible to distinguish between contributions from a local mode and a thermally activated process. A multifrequency study of the relaxation rates of bis(diethyldithiocarbamato)copper(II), [Cu(dtc) 2 ] doped into diamagnetic Ni(dtc) 2 [42], showed that relaxation rates were not frequency dependent, which is consistent with a local mode and inconsistent with a thermally activated process. By analogy with the results for Cu(dtc) 2 a local mode was used to model the data for the copper complexes reported herein.…”
Section: Strategy Used In Analyzing Temperature Dependence Of Tmentioning
confidence: 80%
See 1 more Smart Citation
“…Based only on the temperature dependence of 1/T 1 over a limited temperature interval at a single microwave frequency it is not possible to distinguish between contributions from a local mode and a thermally activated process. A multifrequency study of the relaxation rates of bis(diethyldithiocarbamato)copper(II), [Cu(dtc) 2 ] doped into diamagnetic Ni(dtc) 2 [42], showed that relaxation rates were not frequency dependent, which is consistent with a local mode and inconsistent with a thermally activated process. By analogy with the results for Cu(dtc) 2 a local mode was used to model the data for the copper complexes reported herein.…”
Section: Strategy Used In Analyzing Temperature Dependence Of Tmentioning
confidence: 80%
“…(2) to the temperature dependence of 1/T 1 for 1 was 0.069 with the inclusion of a local mode, but without a local mode it was 0.112. These processes are tentatively assigned to local modes by analogy with the analysis of relaxation rates for Cu(dtc) 2 [42]. Best fits of Eq.…”
Section: Local Modesmentioning
confidence: 99%
“…The remaining factor can be regarded as a constant that characterizes the coupling strength of said mode, Eq. (8). Thus, the total contribution is simply a balance between how populated the mode is and how strong that vibrational mode couples with the spin excitation.…”
Section: Some General Considerationsmentioning
confidence: 99%
“…While they usually fall outside the low-frequency window that can interact with spin states in simple extended ionic lattices considered by physicists, these vibrations become relevant in energy in more complex molecular systems. This way, local vibrations are able to dominate that coupling by: (a) taking the place of acoustic phonons in Raman and Orbach[7(a)] or thermally activated [8] processes, which are also critically important for the relaxation of molecular nanomagnets, and (b) being the main contribution to the spin-lattice decoherence rate 1/T1 around liquid nitrogen temperatures. [9] Owing to the well-known bound T2 ≤ 2T1, this means that the characteristic time T2 will end up being controlled by the spin-lattice relaxation via molecular vibrations beyond those temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As has been shown for some radicals, some relaxation mechanisms cause the relaxation times to be frequency dependent (17)(18)(19). Until now, low-frequency electron spin relaxation measurements have been performed with FID or electron spin echo (ESE) detection.…”
Section: Introductionmentioning
confidence: 98%